FAILED LOCALIZATION IN PRIMARY HYPERPARATHYROIDISM DUE TO POLYGLANDULAR DISEASE - Z, Aina Mardiah; WA, Siti Sanaa; MA, Masliza Hanuni; Mohamad, Hussain; Muda, Nor Hisham (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Primary hyperparathyroidism (PHPT) is characterized by hypercalcemia driven by excess secretion of parathyroid hormone (PTH). While solitary hyperfunctioning parathyroid adenomas account for up to 90% of cases, localizing hyperfunctioning glands in multiglandular disease (MGD) is more challenging. CASE A 46-year-old female presented with chronic vomiting and significant weight loss, leading to a diagnosis of primary hyperparathyroidism with secondary osteoporosis and severe vitamin D deficiency. She had five admissions over 10 months for severe hypercalcemia, (3.6- 4.4 mmol/L) requiring intravenous bisphosphonates. She underwent multiple imaging studies for parathyroid adenoma localization, including parathyroid ultrasound and subsequent sestamibi scan, which showed no evidence of hyperfunctioning parathyroid tissue. A computed tomography scan using a parathyroid protocol did not demonstrate any parathyroid adenoma. After multiple hypercalcaemic crises requiring IV bisphosphonates, oral cinacalcet 50 mg twice daily was initiated to control her hypercalcemia. However, her calcium levels remained elevated, leading to the decision to do bilateral neck exploration (BNE) due to failed multimodal localization studies. Calcitonin (total dosing of 300 units) was administered preoperatively to optimize calcium levels. Intraoperatively, the right superior and left inferior parathyroid glands were removed, preserving only the right inferior parathyroid gland. The left superior parathyroid gland was not visualized. Intraoperative iPTH was not available in our setting. Histopathological examination revealed a right superior parathyroid adenoma and left inferior gland hyperplasia. Postoperatively, she transiently required calcium infusion and was discharged with oral calcium and vitamin D supplementation. Preoperatively, serum intact PTH was 167 pg/mL (NR 14.9-56.9), which decreased to 16.8 pg/mL one month postoperatively, indicating successful removal of the target adenoma. CONCLUSION In cases of failed localization in PHPT, recognizing MGD is crucial. BNE may yield higher cure rates compared to minimally invasive parathyroidectomy, which require two concordant imaging studies. Preoperative calcium optimization is essential for minimizing intraoperative complications and the risk of postoperative hungry bone syndrome.